2017
DOI: 10.1002/aqc.2830
|View full text |Cite
|
Sign up to set email alerts
|

Basin‐scale distribution and haplotype partitioning in different genetic lineages of the Neotropical migratory fish Salminus brasiliensis

Abstract: Four valid species are currently recognized in the Neotropical migratory genus Salminus: Salminus brasiliensis, Salminus franciscanus, Salminus hilarii and Salminus affinis. However, molecular evidence strongly suggested that two different species might be contained under the taxonomic denomination Salminus brasiliensis. Therefore, the geographical distribution of each entity was evaluated in order to understand their contribution to the different stocks of major river networks in South America. Major river ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
(109 reference statements)
0
7
0
1
Order By: Relevance
“…There is a growing concern in the scientific community that simply installing fish passage devices does not guarantee the longterm conservation of migratory fish species (Agostinho, Gomes & Pelicice, 2007;Brown et al, 2013;Silva et al, 2018;Birnie-Gauvin et al, 2019). The loss of critical habitats by river damming and reservoir formation (Du et al, 2013), the reduction in the genetic connectivity of populations (Baggio et al, 2018;Rosso et al, 2018), and the environmental changes caused by dams (Dugan et al, 2010;Tamario et al, 2019) act synergistically to reduce the species capability of persisting in the area affected. The results of this study raise an important question that has received no attention in the literature on management and conservation of neotropical migratory fish species: whether the behaviour of translocated individuals may create an additional challenge to the conservation of the group.…”
Section: Movement Patternsmentioning
confidence: 99%
“…There is a growing concern in the scientific community that simply installing fish passage devices does not guarantee the longterm conservation of migratory fish species (Agostinho, Gomes & Pelicice, 2007;Brown et al, 2013;Silva et al, 2018;Birnie-Gauvin et al, 2019). The loss of critical habitats by river damming and reservoir formation (Du et al, 2013), the reduction in the genetic connectivity of populations (Baggio et al, 2018;Rosso et al, 2018), and the environmental changes caused by dams (Dugan et al, 2010;Tamario et al, 2019) act synergistically to reduce the species capability of persisting in the area affected. The results of this study raise an important question that has received no attention in the literature on management and conservation of neotropical migratory fish species: whether the behaviour of translocated individuals may create an additional challenge to the conservation of the group.…”
Section: Movement Patternsmentioning
confidence: 99%
“…For Machado et al [82] in a study conducted in the South American basins, their results indicated that the genus may consist of different subgroups, and that at least two new species of the genus Salminus exist and await description, totaling seven species in the genus Salminus in the future. Rosso et al [83] evidenced in a study conducted in Argentina, Brazil and Paraguay, the results also indicated that two different putative species could be contained under the taxonomic name Salminus brasiliensis, along with their haplotypes. This leads us to believe that further study on phylogenetic analyses of this emblematic ichthyofaunistic genus is necessary, and that new species; in addition to those mentioned in this study, they may be circulating through the rivers of Brazil reinforcing the idea of more taxonomic units in the genus Salminus in The Brazilian territory.…”
Section: Challenges and Perspectives: Conditions Of Sustainability Ofmentioning
confidence: 81%
“…from unidentified juveniles collected during original samplings in 2011. Molecular analyses also revealed the existence of likely cryptic species within Salminus brasiliensis (Rosso et al., 2018) and Astyanax saguazu . With the revision of voucher material in fish collections, two new records ( Crenicichla minuano and Rineloricaria catamarcensis ) were registered.…”
Section: Resultsmentioning
confidence: 99%